A novel in situ Polymerase chain reaction hybridisation assay for the direct detection of bovine herpesvirus type 5 in formalin-fixed, paraffin-embedded tissues - Cardoso, Tereza C. [UNESP]; Gomes, Deriane E.; Ferrari, Heitor F.; Siva-Frade, Camila; Rosa, Ana C. G.; Andrade, Alexandre Lima de [UNESP]; Luvizotto, Maria Cecilia R. (Elsevier B.V., 2010)
An in situ polymerase chain reaction (IS-PCR) hybridisation assay was carried out on the brains of 20 cattle infected naturally with bovine herpesvirus type 5 (BoHV-5). Sections from the olfactory bulb and the frontal cortex of each sample were analysed using IS-PCR followed by hybridisation targeting the BoHV-5 US9 gene using a biotinylated primer. Each of the IS-PCR and hybridisation steps was optimised, and three different methods for detecting the virus were used. No false positive signals were observed in any negative control sample (n = 20), resulting in a specificity of 100%. The results of IS-PCR hybridisation analysis of the olfactory bulb and the frontal cortex be compared directly with the results obtained using virus isolation, and the specificity and sensitivity were calculated. The most suitable method of visualisation was the peroxidase/3'-3-diaminobenzidine (DAB) detection system coupled with the use of the fluorescent dye Cy3. Using either of these methods, 80% of the positive samples (16 out of 20 samples) were identified using olfactory bulb sections. This is the first report using IS-PCR hybridisation for the direct detection of BoHV-5 DNA in clinical samples, and it provides an additional method for veterinary virology. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bovine herpesvirus type 5; BoHV-5; In situ PCR hybridisation